EFEKTIVITAS ANTIVIRUS OSELTAMIVIR PADA SUBJEK COVID-19 DENGAN ATAU TANPA PENYAKIT PENYERTA DI PUSKESMAS ARUT SELATAN – PANGKALAN BUN - Soufia Ardiani; Abdul Rahem; Anita Purnamayanti (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
South Arut occupies the highest position with 51.55% of the total COVID-19 cases in Kota Waringin Barat, Central Borneo. The purpose of the study was to determine patient characteristics and analyze the effectiveness of oseltamivir in COVID-19 patients. The research design was an observational study and data collected retrospectively. Inclusion criteria were COVID-19 subjects with or without comorbidities and outpatient treatment at the Arut Selatan, Pangkalan-Bun Health Center who were given Oseltamivir. Parameters of therapeutic effectiveness were measured by the WHO Clinical Progression Scale consisting of 5 levels of clinical condition of patients with a score range of 0 (uninfected) – 10 (died). Data analysis was descriptively grouped according to clinical progression scale scores. The results of the study of 107 subjects were mostly male (56.1%) and aged 26-45 years (34.6%). The clinical results of therapy were 0.9% of subjects recovered with negative swab results (score 0), 98.2% improved (score 1), and 0.9% died (score 10). There were no subjects who needed to be referred to the hospital, Self-quarantine of 8-15 days showed 96 (89.7%) subjects experienced clinical improvement, symptoms free, and swab results were negative. It could be concluded that oseltamivir was effective for mild Covid-19 subjects in South Arut, Pangkalan Bun, Kota Waringin, Central Borneo.